2021
DOI: 10.3390/insects12070635
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila suzukii Susceptibility to the Oral Administration of Bacillus thuringiensis, Xenorhabdus nematophila and Its Secondary Metabolites

Abstract: Drosophila suzukii, Spotted Wing Drosophila (SWD), is a serious economic issue for thin-skinned fruit farmers. The invasion of this dipteran is mainly counteracted by chemical control methods; however, it would be desirable to replace them with biological control. All assays were performed with Bacillus thuringiensis (Bt), Xenorhabdus nematophila (Xn), and Xn secretions, administered orally in single or combination, then larval lethality was assessed at different times. Gut damage caused by Bt and the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…In this study, we observed that the three EPN species (Sc, Sf, and Hb) showed variable efficacy on SWD larvae under the different thermal conditions chosen, accounting for their optimal temperature range of use. As previously observed [ 40 , 41 , 42 , 63 ], the species leading to the highest SWD lethality rate was S. carpocapsae (Sc) which, at constant temperature and the highest concentration, induced a mortality rate of 93%. However, when administered under DTF conditions, a reduction in its activity was detected.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this study, we observed that the three EPN species (Sc, Sf, and Hb) showed variable efficacy on SWD larvae under the different thermal conditions chosen, accounting for their optimal temperature range of use. As previously observed [ 40 , 41 , 42 , 63 ], the species leading to the highest SWD lethality rate was S. carpocapsae (Sc) which, at constant temperature and the highest concentration, induced a mortality rate of 93%. However, when administered under DTF conditions, a reduction in its activity was detected.…”
Section: Discussionsupporting
confidence: 61%
“…Among the most commonly used bioinsecticides in SWD control are entomopathogenic nematodes (EPNs) and microorganisms such as Bacillus thuringiensis [ 35 , 40 , 41 , 42 ], thus our purpose was to investigate the efficacy of the nematodes Steinernema carpocapsae (Sc), Steinernema feltiae (Sf), Heterorhabditis bacteriophora (Hb), and the bacterium B. thuringiensis var. kurstaki (Btk), on the larval stages of SWD, under DTF conditions detected in two periods of the year (late spring and summer), corresponding to the reproductive window of SWD in temperate regions such as north and central Italy, where dramatic colonization of agricultural areas with large crops of thin-skinned fruits was detected [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hemolymph was collected in Eppendorf microcentrifuge tubes; to determine cell viability, 10 μL of hemolymph was resuspended with 10 μL of Trypan blue staining solution (1%), then 10 μL of hemolymph were disposed on a Neubauer hemocytometer. Hemocytes were counted using a Corning Cell counter and the data obtained were processed by CytoSmart ® software (Axion Biosystems, Atlanta, CA, USA) [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, many studies on new biocontrol techniques have been carried out in the laboratory [56][57][58][59], still lacking the assessment obtained with field trials and the knowledge transfer from research to industry. The combined use of bioinsecticides (e.g., Bacillus thuringiensis and entomopathogenic nematodes) seems a promising frontier allowing to increase the efficacy of biocontrol methods by reducing the time needed to eradicate pest populations [60,61].…”
Section: Use In Tons (mentioning
confidence: 99%